Handbook of research on sport psychology - 4 0 16; Singer, Robert N.;Murphey, Milledge.;Tennant, L. Keith; 5 International Society of Sports Psychology (New York :;Toronto :;New York : Macmillan ;;Collier Macmillan Canada ;;Maxwell Macmillan International, 1993)
The first book of its kind, the Handbook of Research on Sport Psychology contains an extensive array of chapters on theories, research, and applications authored by a host of international experts. This valuable resource not only covers what is presently known in sport psychology, but extends to the frontiers of investigation, where conclusions have yet to be drawn. The authors emphasize a comprehensive treatment of each research area cited and link findings and methods throughout the Handbook's entire research collection. Ultimately, this book provides its readers with useful theoretical explanations for current findings in sport psychology and guides them to new areas of research activity. The Handbook's forty-four chapters begin with a general orientation on research in sport psychology. The book goes on to cover a variety of specialized areas of research and influence in the field. The second section deals with assessment of skill acquisition, followed by a section on psychological characteristics and high-level performance. Another section deals with social-cognitive dimensions of motivation, leading to a discussion of research on popular psychological techniques that may enhance athletic performance. Social factors such as socialization, moral psychology, and the impact of spectators on athletic performance are addressed, followed by a specific consideration of group structure, leadership, and group psychology. Also assessed are the connections between sport and life-span development, including age, gender, and enhancement of the quality of life. The coverage of specific research topics concludes with discussions on exercise and health psychology. The Handbook goes on to explore research methodology in a stimulating section on psychometrics. Analyses of research paradigms and protocols typically used in sport psychology are provided, as well as suggestions on how to improve current research methods. The final section of the book addresses moral and professional-ethical issues in sport psychology and how they are being resolved today. Extensive bibliographies are appended to chapters throughout the book. The Handbook of Research on Sport Psychology is an invaluable resource for every college and university library, sport psychologist, athlete, and coach. Sport psychology professors should also seriously consider the adoption of this text for their graduate classes and as a sourcebook for research in the field.
I. Overview of Sport Psychology. 1. Overview of Sport Psychology / Richard H. Cox, Yijun Qiu and Zhan Liu. 2. Contemporary Areas of Research in Sport Psychology in Selected Countries. Contemporary Areas of Research in Sport Psychology in France: Overview and Perspectives / Hubert Ripoll and Edgar Thill. Contemporary Areas of Research in Sport Psychology in Germany / Dieter Hackfort. Sport Psychology in Australia: Current Research / Denis Glencross. Sport Psychology in the Former U.S.S.R. / Elena Kantor and Juri Ryzonkin. Contemporary Areas of Research in Sport Psychology in the People's Republic of China / Yijun Qiu and Zhuo-ying Qiu. Contemporary Areas of Research in Sport Psychology in Japan / Atsushi H. Fujita and Soichi Ichimura -- II. Skill Acquisition. 3. Levels of Performance Skill / Craig A. Wrisberg. 4. Developmental considerations in Skill Acquisition / Jerry R. Thomas, Katherine T. Thomas and Jere D. Gallagher. 5. Modeling: Learning, Developmental, and Social Psychological Considerations / Penny McCullagh. 6. Attention / Bruce Abernethy. 7. Decision Making in Sport: A Cognitive Perspective / Gershon Tenenbaum and Michael Bar-Eli. 8. Augmented Feedback in Skill Acquisition / Richard Magill. 9. Arranging Practice Conditions and Designing Instruction / Craig Chamberlin and Timothy D. Lee. 10. Human Skill: Ideas, Concepts, and Models / Denis Glencross -- III. Psychological Characteristics and High-Level Performance. 11. Elite Performance and Personality: From Description and Prediction to Diagnosis and Intervention / Yves Vanden Auweele, Bert De Cuyper, Veerle Van Mele and Randy Rzewnicki. 12. Talent Detection and Development in Sport / Guy Regnier, John Salmela and Storm J. Russell. 13. Competitiveness and Competitive Orientation in Sport / Diane L. Gill. 14. Anxiety / Dieter Hackfort and Peter Schwenkmezger. 15. Aggression / Joel Thirer. 16. Individual Differences: Cognitive and Perceptual Styles / David Pargman -- IV. Social-Cognitive Dimensions of Motivations. 17. Motivation in Sport: Understanding and Enhancing the Motivation and Achievement of Children / Glyn Roberts. 18. Goals: A Social Cognitive Approach to the Study of Achievement Motivation in Sport / Joan L. Duda. 19. Attribution Research and Sport Psychology / Stuart Biddle -- V. Psychological Techniques for Individual Performance. 20. Goal Setting in Sport / Damon Burton. 21. Imagery / Richard Suinn. 22. Optimizing Arousal Levels / Leonard Zaichkowsky and Koji Takenaka. 23. Responding to Competitive Pressure / Robert J. Rotella and J. Dana Lerner. 24. Attention Control Training / Robert N. Nideffer. 25. Self-Regulation Strategies in Sport and Exercise / Debra J. Crews -- VI. Social Influences. 26. Socialization and Sport / Jay Coakley. 27. Moral Psychology in the Context of Sport / Brenda J. Light Bredemier and David L. Light Shields. 28. Spectators: Reactions to Sports Events and Effects on Athletic Performance / Dolf Zillmann and Paul B. Paulus -- VII. Group Dynamics. 29. Social Interactions / Stephanie Hanrahan and Cindy Gallois. 30. Leadership / P. Chelladurai. 31. Group Cohesion in Sport and Exercise / W. Neil Widmeyer, Albert V. Carron and Lawrence R. Brawley -- VIII. Life-Span Development. 32. Youth in Sport: Psychological Considerations / Robert J. Brustad. 33. Gender and Sport / Carole A. Oglesby and Karen L. Hill. 34. Exercise and the Quality of Life / Bonnie G. Berger and Adrian McInman. 35. Career Termination Issues Among Elite Athletes / Bruce Ogilvie and Jim Taylor -- IX. Exercise/Health Psychology. 36. Exercise Adherence / Rod K. Dishman. 37. Emotion and Aerobic Exercise / Steve Boutcher. 38. Psychology of Injury and Injury Rehabilitation / Jean Williams and Nancy Roepke. 39. Overtraining and Staleness: Psychometric Monitoring of Endurance Athletes / John S. Raglin. 40. Psychology of Drug Use in Sport / Mark H. Anshel. 41. Psychological/Behavioral Effects of Anabolic-Androgenic Steroids / Michael S. Bahrke and Charles E. Yesalis -- X. Psychometrics. 42. Sport-Specific and Culturally Adapted Measures in Sport and Exercise Psychology Research: Issues and Strategies / Lise Gauvin and Storm J. Russell. 43. Use, Misuse, and Disuse of Psychometrics in Sport Psychology Research / Robert W. Schutz and Marc E. Gessaroli -- XI. Professional Ethics in Sport Psychology. 44. Professional Ethics in Sport Psychology / Michael L. Sachs.
Includes bibliographical references and indexes.
Keywords: 2 -- 0; 6; Psychological aspects.;Research.;psychology. -- Sports;Sports;Sports -- 20; 20; 2